Treatment Outcomes of IL-17 Inhibitors in Hidradenitis Suppurativa: A Systematic Review. Issue 1 (January 2022) - Kashetsky, Nadia; Mufti, Asfandyar; Alabdulrazzaq, Shaikhah; Lytvyn, Yuliya; Sachdeva, Muskaan; Rahat, Abdullah; Yeung, Jensen
The IL-17 pathway is a potential therapeutic target shown to be implicated in hidradenitis suppurativa (HS), however, it remains unclear whether evidence from mechanistic studies may translate into clinical practice. This systematic review summarizes available treatment outcomes of IL-17 inhibitors in patients with HS. Embase, MEDLINE, PubMed, and clinicaltrials.gov were comprehensively searched on February 26, 2021 to include 16 original studies representing 128 patients with HS (mean age: 36.5 years; age range: 21-47 years; male: 50.0%). Treatment outcomes were reported for the following biologics: secukinumab ( n = 105), brodalumab ( n = 22), and ixekizumab ( n = 1). Patients were classified as responders or non-responders according to achievement of a positive response/improvement based on criteria established for each included study. For secukinumab 57.1% ( n = 60/105) of patients were responders in a mean response period of 16.2 weeks and 42.9% ( n = 45/105) were non-responders; for brodalumab, 100.0% ( n = 22/22) of patients were responders within 4.4 weeks; and the one patient treated with ixekizumab was a responder within 10 weeks. In conclusion, IL-17 inhibitors may serve as an effective therapeutic target in approximately two-thirds of patients with HS and can be considered in those who are refractory to other treatment modalities. We also stress the importance of consistent outcome measures to enhance evidence synthesis, decrease reporting bias, provide potential for future meta-analysis, and ultimately improve clinical outcomes for patients with HS.